Fast mode selection of intra prediction algorithm based on spatial and frequency analysis - Shu-bo ZHAN; Jian-bin SONG; Li MA; Fang-chun YANG (Tongxin xuebao)
By using of the features of DCT coefficients in frequency domain and the correlation of the predictive mode in spatial domain,the proposed algorithm evaluated the complexity of encoding block and selected encoding block size firstly,computed the texture direction and pre-selected most possibly prediction mode of 16×16 block secondly,and then got the neighbor block’s optimum mode and narrowed mode selection range of 4×4 block.The experiments show that,compared with existing algorithms,in the case of almost equal quality,the speed of the algorithm is significantly improved.